The Role of Teachers in Shaping Students' Religious Character - Ridha Dwi Minanti (Sufiya Journal of Islamic Studies, 2024)
This study examines the role of teachers in the formation of students' religious character in MTsS Nurul Amaliyah. In the midst of increasing concerns about student delinquency and weakening moral values, the formation of religious character has become a central issue in educational discourse. This research uses a qualitative approach, with data collection techniques in the form of direct observation, in-depth interviews with teachers and principals, as well as documentation and literature studies from journals, theses, books, and field notes. The results of the study show that teachers have an important role, not only through the religious learning process, but also through the habit of good speech, the provision of moral advice, and discipline that is carried out consistently. Students' religious character is formed through the integration of formal learning and ongoing religious practices in daily life at school. These findings confirm that character formation is not only obtained from the subject matter, but also from the examples and real experiences that teachers continue to foster in the school environment.